Efficacy of topical Calendula officinalis on prevalence of radiation‐induced dermatitis: A randomised controlled trial. (23rd September 2020) - Siddiquee, Shihab; McGee, Margaret A; Vincent, Andrew D; Giles, Eileen; Clothier, Robyn; Carruthers, Scott; Penniment, Michael
Abstract: Objectives: A randomised controlled trial was undertaken to compare the efficacy of topical Calendula officinalis (Calendula) versus standard of care (Sorbolene: 10% glycerine in cetomacragol cream) in reducing the prevalence of radiation‐induced dermatitis in women undergoing breast cancer radiotherapy. Methods: A total of 271 women were screened and 82 were randomised. The primary outcome was prevalence of acute radiation‐induced dermatitis (RTOG grade 2+) assessed at multiple skin sites. A chi‐squared test was conducted for the primary outcome with a worst‐case scenario imputation. Results: The recruitment target ( n = 178) was not achieved. A total of n = 81 participants were analysed ( n = 40 Calendula; n = 41 Sorbolene). There was no detectable difference in prevalence of radiation‐induced dermatitis grade 2+ between the Calendula (53%) and Sorbolene (62%) groups (primary analysis OR = 0.87, 95% CI: [0.36, 2.09], P = 0.92; covariate adjusted complete case analysis OR 0.40, 95% CI: [0.13, 1.20], P = 0.10). Conclusion: This randomised controlled trial showed no difference between Calendula and standard of care (Sorbolene) for the prevention of radiation‐induced dermatitis. However, the study was underpowered (limited recruitment) for the primary comparison.